On Mixed Convection Squeezing Flow of Nanofluids - Sheikh Irfan Ullah Khan; Ebraheem Alzahrani; Umar Khan; Noreena Zeb; Anwar Zeb (Energies, 2020)
In this article, the impact of effective Prandtl number model on 3D incompressible flow in a rotating channel is proposed under the influence of mixed convection. The coupled nonlinear system of partial differential equations is decomposed into a highly nonlinear system of ordinary differential equations with aid of suitable similarity transforms. Then, the solution of a nonlinear system of ordinary differential equations is obtained numerically by using Runge–Kutta–Fehlberg (RKF) method. Furthermore, the surface drag force <semantics> C f </semantics> and the rate of heat transfer <semantics> N u </semantics> are portrayed numerically. The effects of different emerging physical parameters such as Hartmann number (M), Reynold’s number (Re), squeezing parameter ( <semantics> β </semantics> ), mixed convection parameter <semantics> λ </semantics> , and volume fraction ( <semantics> φ </semantics> ) are also incorporated graphically for <semantics> γ — </semantics> alumina. Due to the higher viscosity and thermal conductivity ethylene-based nanofluids, it is observed to be an effective common base fluid as compared to water. These observations portrayed the temperature of gamma-alumina ethylene-based nanofluids rising on gamma-alumina water based nanofluids.